2022
DOI: 10.1002/1873-3468.14485
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of small molecule redox homeostasis in mitochondria

Abstract: Compartmentalisation of eukaryotic cells enables fundamental otherwise often incompatible cellular processes. Establishment and maintenance of distinct compartments in the cell relies not only on proteins, lipids and metabolites but also on small redox molecules. In particular, small redox molecules such as glutathione, NAD(P)H and hydrogen peroxide (H 2 O 2 ) cooperate with protein partners in dedicated machineries to establish specific subcellular redox compartments with conditions that enable oxidative prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 178 publications
(235 reference statements)
0
2
0
Order By: Relevance
“…Retention of intracellular GSH levels may be a critical factor in the ROS scavenging effect of morroniside against H2O2. GSH exists not only in the cytoplasm but also in mitochondria, and protects mitochondria from oxidative stress by scavenging ROS generated during electron transport and oxidative phosphorylation within mitochondria (Jacobs and Riemer, 2023). Recently, Li et al (2023) found that morroniside can reduce ROS production by restoring the mitochondrial respiratory chain in a Parkinson's disease model.…”
Section: Discussionmentioning
confidence: 99%
“…Retention of intracellular GSH levels may be a critical factor in the ROS scavenging effect of morroniside against H2O2. GSH exists not only in the cytoplasm but also in mitochondria, and protects mitochondria from oxidative stress by scavenging ROS generated during electron transport and oxidative phosphorylation within mitochondria (Jacobs and Riemer, 2023). Recently, Li et al (2023) found that morroniside can reduce ROS production by restoring the mitochondrial respiratory chain in a Parkinson's disease model.…”
Section: Discussionmentioning
confidence: 99%
“…Experimentally, the lack of GPX1 and SOD2 genes affects the tissue mitochondria, leading to oxidative stress in mice [76]. Overall, SOD2 converts oxygen radicals into hydrogen peroxide, causing mitochondrial dysfunctions [77]. The antioxidative enzymes, i.e., superoxide dismutase (SOD2) and glutathione peroxidase (GPX1), produce the first line of defense actions against free radicals and pathogens [78].…”
Section: Discussionmentioning
confidence: 99%
“…The mitochondrial NADPH is central to ROS production and the reduction in thiols (-SH). Numerous protein functions are controlled by the reduction in -SH [115]. In line with cancer signaling, NADPH-Thioredoxin-1 (Trx-1) is instrumental in activating Apurinic/apyrimidinic endonuclease 1 (APE-1), which is a key regulator for various cancer signaling junctions such as nuclear factor-κB (NF-κB), NRF2, protein-53 (p53), Redox effector factor-1 (Ref1), estrogen receptor and glucocorticoid receptor [116,117].…”
Section: Mitochondria Regulation Of Redox Balancementioning
confidence: 99%